Psychometric properties of the Dundee Ready Educational Environment Measure (DREEM) in a Moroccan sample of nursing students - Saka Khadija; Mohamed-Yassine Amarouch; Youssef Miyah; Mohammed Benjelloun; Jaouad El-Hilaly (Belitung Nursing Journal)
Background: The educational environment is crucial to student learning and professional development in nursing education. The Dundee Ready Educational Environment Measure (DREEM) is a widely used tool for assessing educational environments in health professions. However, its psychometric properties have not been sufficiently evaluated in the Moroccan context, particularly among nursing students.